Multicultural encounters within kampus merdeka: A study on educational policy impact to bolster diversity - Suharno Suharno; Rifai Rifai; Ajat Sudrajat (Jurnal Cakrawala Pendidikan, 2023)
The future of Indonesian diversity is influenced partly by educational design and policy. In that sense, this study aims to analyze the actual and potential impacts of Kampus Merdeka's educational policy in strengthening multicultural encounters. Based on a specific context of Yogyakarta State University or Universitas Negeri Yogyakarta (UNY), Indonesia, this study used the qualitative method to reveal the Merdeka Belajar-Kampus Merdeka (MBKM)/Freedom of Learning Kampus Merdeka program in providing both actual and potential multicultural encounters, particularly in the Faculty of Social Sciences. The determination of research subjects was combining purposive and snowball sampling. The data analysis technique utilized an inductive approach for qualitative data analysis. The stages of data analysis consisted of data reduction, data display, conclusion, and verification, while validity checking employed triangulation. The study concludes that the MBKM program provides an experience and a cross-ethnic encountering spaces for students to share each other's diversity of identities. The encounters are through the three-semester learning rights program outside the study program. Cross-identity encounter in the MBKM program also allows students to combine aspects of concern for structural and cultural issues through a derivative program of three-semester learning rights outside the study program. The actual impacts of the MBKM program include providing spaces of strengthening multiculturalism, through students-exchanges, Center of Excellence (CoE) facilitation, and equal education for all. In addition, the needed regulations have been issued to provide the potential impacts to optimize for multicultural encounters through student exchanges, especially intercultural understanding or multicultural collaboration programs.